Continuous Mid-Infrared Star Formation Rate Indicators. Issue Volume 10:Issue S309(2014) (9th February 2015) - Battisti, A. J.; Calzetti, D.; Johnson, B. D.; Elbaz, D.
Abstract: We present continuous, monochromatic star formation rate (SFR) indicators over the mid-infrared wavelength range of 6–70 μm. We use a sample of 58 star forming galaxies (SFGs) in the Spitzer -SDSS- GALEX Spectroscopic Survey (SSGSS) at z <0.2, for which there is a rich suite of multi-wavelength photometry and spectroscopy from the ultraviolet through to the infrared. The data from the Spitzer infrared spectrograph (IRS) of these galaxies, which spans 5–40 μm, is anchored to their photometric counterparts. The spectral region between 40-70 μm is interpolated using dust model fits to the IRS spectrum anchored by Spitzer 70 and 160 μm photometry. Since there are no sharp spectral features in this region, we expect these interpolations to be robust. This spectral range is calibrated as a SFR diagnostic using several reference SFR indicators to mitigate potential bias. Our band-specific continuous SFR indicators are found to be consistent with monochromatic calibrations in the local universe, as derived from Spitzer, WISE, and Herschel photometry. Additionally, in the era of the James Webb Space Telescope this will become a flexible tool, applicable to any SFG up to z ∼3.